Initial report of a phase II study with R-FND followed by ibritumomab tiuxetan radioimmunotherapy and rituximab maintenance in patients with untreated high-risk follicular lymphoma. Issue 1 (2nd January 2021) - Samaniego, Felipe; McLaughlin, Peter; Neelapu, Sattva S.; Feng, Lei; Fanale, Michelle; Nastoupil, Loretta; Rodriguez, Maria Alma; Pro, Barbara; Taylor, Erin; Hagemeister, Fredrick B.; Fowler, Nathan
Abstract: R-FND (rituximab, fludarabine, mitoxantrone, and dexamethasone) can induce molecular remissions in indolent lymphoma. The addition of 90 yttrium ibritumomab tiuxetan ( 90 YIT) radioimmunotherapy following first-line induction treatment in patients with advanced follicular lymphoma (FL) may improve remission rates. We now report 10-year follow-up results from our sequential treatment approach with an abbreviated regimen of R-FND followed by 90 YIT consolidation and rituximab maintenance. Forty-nine patients were enrolled; 47 received treatment. Patients had high-risk (FLIPI score ≥3) FL of grade 1–3A and stage III/IV with adequate hematologic function. Following R-FND, the complete and partial response rates were 91% and 8.5%, respectively. After 90 YIT consolidation, the CR rate increased to 97%. The 10-year PFS rate was 49%. The most common non-hematologic, grade 3 or 4 adverse events were fatigue, dyspnea, and myalgia. Five developed myelodysplastic syndrome (MDS). This treatment approach is most appropriate in FLIPI-based high-risk patients whose outlook with standard therapy is inadequate.